Tasmannia insipida R.Br. Ex DC. Leaf Extracts Inhibit the Growth of the Acne Vulgaris Causing Bacterium Cutibacterium acnes - Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Acne vulgaris is a skin conditions that affects most adolescents and also afflicts some adults. Medicinal plant extracts may provide leads for the development of new topical and/ or oral therapies for acnes vulgaris, yet many traditional medicine plants are yet to be screened for growth inhibitory activity against Cutibacterium acnes (the major bacterial cause of acne). Materials and Methods: Methanolic and aqueous Tasmannia insipida R.Br. ex DC. Leaf extracts were investigated by disc diffusion and liquid dilution MIC assays against Cutibacterium acnes. Toxicity was determined using Artemia franciscana nauplii bioassays. Results: Methanolic and aqueous T. insipida leaf extracts displayed noteworthy bacterial growth inhibitory activity against C. acnes growth. The methanolic T. insipida leaf extract had particularly good antibacterial effects against C. acnes, with an LD MIC value of 752 μg/mL. Slightly higher LD MIC values were noted for the aqueous T. insipida leaf extract against C. acnes (LD MIC=1250 μg/mL). The methanolic and aqueous T. insipida leaf extracts were nontoxic in the Artemia franciscana bioassay, with LC50 values substantially >1000 μg/mL. Conclusion: The lack of toxicity of the methanolic and aqueous T. insipida leaf extracts and their noteworthy inhibition of C. acnes growth indicate their potential to alleviate acne vulgaris. Further studies are warranted to isolate and identify the active components and to determine their antibacterial mechanism.
Keywords: Winteraceae; Brush Pepperberry; Australian Medicinal Plants; Acne Vulgaris; Skin Infection; Skin Inflammation; Cutibacterium acnes; Artemia lethality assay